Risk Criticism : Precautionary Reading in an Age of Environmental Uncertainty - Wallace, Molly (Book collections on Project MUSE., 2016)
'Risk Criticism: Reading in an Age of Manufactured Uncertainties' is a study of literary and cultural responses to global environmental risk that offers an environmental humanities approach to understanding risk in an age of unfolding ecological catastrophe. 'Risk Criticism: Reading in an Age of Manufactured Uncertainties' is a study of literary and cultural responses to global environmental risk that offers an environmental humanities approach to understanding risk in an age of unfolding ecological catastrophe. In 2015, the Bulletin of the Atomic Scientists re-set its iconic Doomsday Clock to three minutes to midnight, as close to the apocalypse as it has been since 1953. What pushed its hands was, however, not just the threat of nuclear weapons, but also other global environmental risks that the Bulletin judged to have risen to the scale of the nuclear, including climate change and innovations in the life sciences. If we may once have believed that the end of days would come in a blaze of nuclear firestorm (or the chill of the subsequent nuclear winter), we now suspect that the apocalypse may be much slower, creeping in as chemical toxin, climate change, or bio- or nano- technologies run amok. Taking inspiration from the questions raised by the Bulletin's synecdochical "nuclear," 'Risk Criticism' aims to generate a hybrid form of critical practice that brings "nuclear criticism"--A subfield of literary studies that has been, since the Cold War, largely neglected--into conversation with ecocriticism, the more recent approach to environmental texts in literary studies. Through readings of novels, films, theater, poetry, visual art, websites, news reports, and essays, 'Risk Criticism' tracks the diverse ways in which environmental risks are understood and represented today